Effect of soil management on its radioisotopic composition - Dołhańczuk-Śródka, Agnieszka; Ziembik, Zbigniew; Kusza, Grzegorz (Geology, Geophysics and Environment, 2015)
Radioactive isotopes, both natural and artificial, present in the environment may be convenient indicators that can be used to study a number of physical and chemical processes and transport of pollutants in the ecosystem. The main aim of the study was to evaluate the impact of the type of soil use on the radioisotopic composition in its surface layers. The radioisotopic compositions of surface soil samples collected in the area of a cement plant abandoned for over 20 years and in the area of the nearby allotments were examined and compared. Calculations were performed using methods designed to study compositional variables. The results confirmed a significant impact of usage on the radioisotopic composition of the surface soil layers. However, some characteristics of the composition were common to both locations. It has been found that a significant proportion of the lead isotope - Pb-210, derived from atmospheric deposition. Other radioisotopes remain relatively close to equilibrium in their decay chains. The project was financed by the National Science Centre based on the decision number DEC-2011/03/D/ST10/05392.